Polybius: Experience and the Lessons of History - Moore, Daniel (Historiography of Rome and Its Empire, 2020)
The Greek historian Polybius (2nd century B.C.E.) produced an authoritative history of Rome's rise to dominance in the Mediterranean that was explicitly designed to convey valuable lessons to future generations. But throughout this history, Polybius repeatedly emphasizes the incomparable value of first-hand, practical experience. In Polybius: Experience and the Lessons of History, Daniel Walker Moore shows how Polybius integrates these two apparently competing concepts in a way that affects not just his educational philosophy but the construction of his historical narrative. The manner in which figures such as Hannibal, Scipio Africanus, or even the Romans as a whole learn and develop over the course of Polybius' narrative becomes a critical factor in Rome's ultimate success.